Deep brain stimulation in a patient with progressive myoclonic epilepsy and ataxia due to potassium channel mutation (MEAK). A case report and review of the literature - Michał Sobstyl; Nina Kożuch; Magdalena Iwaniuk-Gugała; Angelika Stapińska-Syniec; Magdalena Konopko; Paweł Jezierski (Epilepsy & Behavior Reports, 2023)
Progressive myoclonic epilepsy (PME) is characterized by prominent myoclonus, generalized tonic-clonic seizures, and less often focal, tonic, or absence seizures. The KCNC1 mutation is responsible for specific clinical phenotype of PME which has been defined as myoclonic epilepsy and ataxia due to potassium channel mutation (MEAK). We present a case of a 44 years-old male patient with genetically proven MEAK who underwent subthalamic nucleus/substantia nigra (STN/SNr) deep brain stimulation (DBS) for his pharmacological-refractory myoclonus and drug-resistant epilepsy (DRE). Since the age of 4–5 years, the patient had been suffering from intention tremor, and later the myoclonic jerks, ataxia involving the upper limbs and walking difficulties worsened. The first bilateral tonic-clonic seizure (BTCS) occurred at the age of 22. The patient agreed to staged bilateral implantation of DBS electrodes placed in the STN/SNr region. The follow-up lasts more than 24 months. The myoclonic jerks assessed by Unified Myoclonus Rating Scale (UMRS) were reduced by nearly 70 % and BTCS was completely abolished. The patient’s ataxia and dysarthria did not improve. Early diagnosis with genetic testing may significantly help in counseling patients with PME and enables to undertake the surgical approach targeting the STN/SNr.